Dienogest suppresses the activation of primordial follicles and preserves the primordial follicle stockpile for fertility in mice. Issue 4 (April 2018) - Zheng, Luyi; Kimura, Fuminori; Wu, Di; Morimune, Aina; Niwa, Yoko; Mita, Shizuka; Takahashi, Kentaro; Murakami, Takashi
Abstract: The aim of the present study was to characterize the effect of long-term usage of dienogest, a fourth-generation progestin that possesses progestogen and anti-androgen activities, on the stockpile of oocytes and fertility after administration. Female ICR mice (100 days old) were divided into a dienogest group and a control group. The mice received 16 consecutive subcutaneous injections of 5 mg dienogest dissolved in corn oil or corn oil as a vehicle control every 4 days. The mice treated with dienogest had more total offspring and larger litter sizes after the final administration than the mice treated with the vehicle control. Greater numbers of primordial follicles were detected at both 4 and 80 days after the final administration. No significant differences were found in serum anti-Müllerian hormone concentrations at 4 and 80 days after the final dienogest administration. The ratio of primary to primordial follicles was decreased in 3-day-old newborn ovaries cultured for 4 days with dienogest (10 –7, 10 –6 and 10 –5 mol/l) compared with ovaries cultured without dienogest. The results of the present study indicate that dienogest suppresses the activation of primordial follicles during its administration and preserves the primordial follicle stockpile and subsequent fertility in mice.